Effectiveness of Virtual STEM Laboratories for Enhancing High School Students' Creativity and STEM Literacy - Nurul Fitri Rahmadani; Sri Retno Dwi Ariani; Sri Mulyani; Nurma Yunita Indriyanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
The Virtual STEM Laboratory is a contextual experimental simulation learning tool that integrates science, technology, engineering, and mathematics (STEM) concepts. This study aims to investigate the Virtual STEM Laboratory's effectiveness in enhancing high school students' STEM literacy and creativity. STEM literacy is defined as the ability of a student to apply, identify, and integrate STEM concepts to solve complex problems and innovate in various areas. Meanwhile, creativity refers to the capability to generate novel and valuable ideas or solutions. The study used an experimental design with a control group to compare the effectiveness of the Virtual STEM Laboratory. In addition, students' STEM literacy and creativity were measured using posttest scores. The results showed that the experimental group had higher STEM literacy and creativity scores compared to the control group, which indicates the effectiveness of the Virtual STEM Laboratory. The study found that the Virtual STEM Laboratory improved STEM literacy as measured by the independent t-test and Kruskal Wallis test with a significance value of 0.000. This suggests that the experimental group had better STEM literacy skills than the control group. The Virtual STEM Laboratory was also found to be effective in enhancing student creativity as measured by the independent t-test with a significance value of 0.000, which implies that the experimental group generated more novel and valuable ideas than the control group. The study confirms the Virtual STEM Laboratory's effectiveness in enhancing high school students' STEM literacy and creativity. The Virtual STEM Laboratory is a valuable tool that can improve students' STEM literacy and creativity, thus contributing to their academic and professional development. Further studies can be conducted to explore the potential of the Virtual STEM Laboratory in enhancing other aspects of STEM education.